The fastest way to fall [large type] - Williams, Denise, 1982- (Center Point Pub, 2022)
"Britta didn't plan on falling for her personal trainer, and Wes didn't plan on Britta. Plans change and it's unclear if love, career, or both will meet them at the finish line. Britta Colby works for a lifestyle website, and when tasked to write about her experience with a hot new body-positive fitness app that includes personal coaching, she knows it's a major opportunity to prove she should write for the site full-time. As CEO of the FitMe app, Wes Lawson finally has the financial security he grew up without, but despite his success, his floundering love life and complicated family situation leaves him feeling isolated and unfulfilled. He decides to get back to what he loves-coaching. Britta's his first new client and they click immediately. As weeks pass, she's surprised at how much she enjoys experimenting with her exercise routine. He's surprised at how much he looks forward to talking to her every day. They convince themselves their attraction is harmless, but when they start working out in person, Wes and Britta find it increasingly challenging to deny their chemistry and maintain a professional distance. Wes isn't supposed to be training clients, much less meeting with them, and Britta's credibility will be sunk if the lifestyle site finds out she's practically dating the fitness coach she's reviewing. Walking away from each other is the smartest thing to do, but running side by side feels like the start of something big"--